The rich, the poor, and the taxes they pay - Pechman, Joseph A., 1918-1989 (Routledge, 2019)
This book presents a selection of essays on public finance, which is concerned with taxation, income maintenance, and social security, with emphasis on the analysis of policy alternatives to improve tax and transfer systems. It is useful for those who are interested in learning tax policy issues.